2008
DOI: 10.1007/s00586-008-0835-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial atlanto-odontoid joint replacement through a transoral approach

Abstract: Resection of the odontoid process and anterior arch of the atlas results in atlantoaxial instability, which if left uncorrected may lead to severe neurological complications. Currently, such atlantoaxial instability is corrected by anterior and/or posterior C1-C2 fusion. However, this results in considerable loss of rotation function of the atlantoaxial complex. From the viewpoint of retaining the rotation function and providing stability, we designed an artificial atlanto-odontoid joint based on anatomical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…It is believed that the ROM in the NZ is more sensitive for assessment of stability 20–22 . In this study, biomechanical analysis of three‐dimensional movement in human cervical spine specimens showed that the ROM in flexion, extension, lateral bending and rotation after AAOJ arthroplasty was definitely decreased compared with anterior decompression, but the ROM of rotation and the range of the NZ were close to normal, these findings being the same as those reported by Lu et al 2,3 …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is believed that the ROM in the NZ is more sensitive for assessment of stability 20–22 . In this study, biomechanical analysis of three‐dimensional movement in human cervical spine specimens showed that the ROM in flexion, extension, lateral bending and rotation after AAOJ arthroplasty was definitely decreased compared with anterior decompression, but the ROM of rotation and the range of the NZ were close to normal, these findings being the same as those reported by Lu et al 2,3 …”
Section: Discussionsupporting
confidence: 84%
“…It is believed that the ROM in the NZ is more sensitive for assessment of stability [20][21][22] . In this study, biomechanical analysis of three-dimensional movement in human cervical spine specimens showed that the ROM in flexion, extension, lateral bending and rotation after AAOJ arthroplasty was definitely decreased compared with anterior decompression, but the ROM of rotation and the range of the NZ were close to normal, these findings being the same as those reported by Lu et al 2,3 . The abovementioned results may be due to the following factors: (i) the distance between the apical odontoid ligament and basion was kept close to normal to ensure a normal ROM of the occipitocervical region in anterior flexion (in the normal occipitocervical spine, anterior flexion is subject to contact between the apical odontoid ligament and basion, and posterior extension is confined by contact between the base of the occipital bone and posterior arch of the atlas, and traction on the tectorial membrane); (ii) the locking link of the atlanto-odontoid joint was rebuilt to ensure that the axis of rotation was restricted to the joint itself, so that various types of movement occurred as they do under normal conditions and the remaining joint capsule and ligaments maintained their normal functions; and (iii) excessive sliding (right/left or front/back) was restricted, because movement of the normal atlantoaxial joint at different angles is coupled with sliding and the ROM of sliding also constrains the ROM of angular movement to a certain extent.…”
Section: Biomechanical Properties Of Three-dimensional Movement Aftersupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the width of the C1 lateral mass is 12.86 ± 0.87 mm. The same parameter was measured as 9.5 ± 1.0 mm by Rocha et al (13), and 14.1 ± 1.5 mm by Lu et al (12).…”
Section: Parameters Mean ± Sd(mm)mentioning
confidence: 60%
“…For the biomechanical study of artificial joints in the spine, human cadavers [21], [22] and animal models have been well studied. Human cadavers have the same biomechanical properties as living humans, but they are precious and their use raises ethical issues; furthermore, they cannot be used to evaluate the in vivo reactions of human vertebrae with artificial joints.…”
Section: Discussionmentioning
confidence: 99%